Development of A Career Understanding Application for Elementary School Students Based on Augmented Reality - Rahim, Maryam; Hulukati, Wenny; Korompot, Salim; Wantu, Tuti; Lakadjo, Mohamad Awal (LPPM Universitas Pendidikan Mandalika, 2024)
This research aims to develop an augmented reality-based career understanding of media for elementary school students. The research and development procedure consists of 7 steps out of 10 main steps, namely: (1) potential and problems, (2) data collection, (3) product design, (4) design validation, (5) product/design revision, (6) products trial, (7) product revisions. Data were collected using a questionnaire consisting of (1) an expert validation questionnaire (guidance and counseling media expert, career guidance and counseling expert, Indonesian language expert), and (2) a small group trial questionnaire (elementary school teachers). Data analysis uses qualitative analysis to analyze data from expert validation and small group trials distributed through the instrument. The research results show that the research product in the form of augmented reality-based career understanding media containing content from 17 professional fields is suitable for use to improve elementary school students' career understanding, considering that this product has been validated through expert validation and small group trials. The implications of the results of this study emphasize the importance of career understanding in elementary schools, to shape children's future aspirations based on augmented reality (AR) as an interactive media for career guidance services in schools, thereby increasing students' interest in various job professions that change career guidance service methods to be more modern as well as developing students' technological competencies in facing the digital era as part of Generation Z and Alpha. Practically, guidance and counseling teachers can improve students' understanding of various professions through AR technology that facilitates understanding of the duties and responsibilities of job professions, schools can also integrate this application into a technology-based curriculum, encourage project-based learning, and inspire students' creativity and innovation in exploring and designing future careers.